The health psychology handbook practical issues for the behavioral medicine specialist - Cohen, Lee M. (Lee Michael), 1972-; McChargue, Dennis E.; Collins, Frank L., Jr.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2003)
Featuring a stellar collection of authors, this comprehensive yet practical sourcebook consolidates information needed by health psychologists working alongside other healthcare professionals in a medical setting to conduct research and to provide clinical assessment and behavioural treatment services.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Clinical health psychology; Electronic books